"New Awakenings Everywhere: Free Jazz Pathways Through Western Europe"* by Ekkehard Jost (1938–2017). (1st September 2017) - Waters, Keith
ABSTRACT: Ekkehard Jost (1938–2017) was one of the world's leading scholarly voices on the development of free jazz, perhaps best known for his seminal text Free Jazz (originally published in 1974). This article presents a chapter from Jost's 2012 book Jazzgeshichten aus Europa ( Jazz Histories of Europe ). In this chapter, translated by Keith Waters, Jost focuses on the development of free jazz in Western Europe during the critical period of the late 1960s and 1970s.